Publish: The How-to Magazine of Desktop Publishing; Personal Publishing: The Magazine for Desktop Publishers; PC Publishing:The Desktop Publishing Magazine for IBM & Compatible PC Users - Jim Shaner; Jim King; Darcy Meeker (Journal of Applied Communications, 1987)
Reviews of Publish: The How-to Magazine of Desktop Publishing; Personal Publishing: The Magazine for Desktop Publishers; PC Publishing: The Destop Publishing Magazine for IBM & Compatible PC Users; People's Workbook: Environmental and Development Agency (EDA) ; "Technology and Learning," from Lawrence Erlbaum Associates ; Instructional Technology: Foundations, edited by Robert M. Gagne; "Art for Art's Sake," by Alfie Kahn.